2013
DOI: 10.1093/neuonc/not049
|View full text |Cite
|
Sign up to set email alerts
|

Early post-bevacizumab progression on contrast-enhanced MRI as a prognostic marker for overall survival in recurrent glioblastoma: results from the ACRIN 6677/RTOG 0625 Central Reader Study

Abstract: Early progression on 2D-T1 and 3D-T1, but not FLAIR MRI, after 8 and 16 weeks of anti-vascular endothelial growth factor therapy has highly significant prognostic value for OS in recurrent GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 51 publications
2
59
1
Order By: Relevance
“…31 In a recent phase II clinical trial, FLAIR and postcontrast T1-weighted imaging were evaluated for their ability to predict overall survival in patients with recurrent glioblastoma multiforme treated with the anti–vascular endothelial growth factor drug bevacizumab. 32 It was found that an increase in enhancement was associated with poorer survival, while FLAIR progression did not reveal a significant survival disadvantage. 32 The results of this study are promising in predicting treatment failure for those who show progression on T1-weighted imaging, yet standard imaging has still remained ineffective in determining true responders from pseudoresponders in those who have diminished enhancement.…”
Section: Discussionmentioning
confidence: 97%
“…31 In a recent phase II clinical trial, FLAIR and postcontrast T1-weighted imaging were evaluated for their ability to predict overall survival in patients with recurrent glioblastoma multiforme treated with the anti–vascular endothelial growth factor drug bevacizumab. 32 It was found that an increase in enhancement was associated with poorer survival, while FLAIR progression did not reveal a significant survival disadvantage. 32 The results of this study are promising in predicting treatment failure for those who show progression on T1-weighted imaging, yet standard imaging has still remained ineffective in determining true responders from pseudoresponders in those who have diminished enhancement.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the high variability of ORRs, there is an association of OR status and OS as demonstrated in our landmark analysis for both criteria. Recently, in a study of imaging data from a phase II trial (RTOG0625) of bevacizumab with irinotecan or temozolomide in recurrent glioblastoma, Boxerman and colleagues demonstrated that early progression at 8 weeks posttreatment based on both two-dimensional and three-dimensional measurements of enhancement, rather than response, was a significant prognostic marker for OS (16). This result suggests that the association of OR and OS observed in our study could be due to including early progressors in the nonresponder group, rather than directly result from the OR status as determined by Macdonald or RANO criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, determination of radiographic progression relative to the gold standard provided by histopathologic confirmation has not been validated for either the Macdonald criteria or the RANO criteria in prospectively conducted clinical trials. Nonetheless, the value of adding T2/FLAIR assessment to the Macdonald criteria remains to be determined, although preliminary evidence of benefit has been suggested previously (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…However, no difference in OS was found in a study of HGG patients treated with the anti-angiogenic drug bevacizumab with improved versus stable contrast enhancement, raising the possibility that pseudoresponse was degrading the prognostic significance of tumor size measurements that are based on contrast-enhancing tissue. 45 This difficulty was addressed with the use of DSC, which could stratify survival in patients with improved or stable contrast enhancement, as shown in a follow-up study. 46 Although this finding has been disputed, and may depend on timing of perfusion imaging, 47 it remains a possibility that the incorporation of perfusion metrics in trials of antiangiogenic therapy could be beneficial in predicting outcome.…”
Section: Clinical Applications Of Advanced Mrimentioning
confidence: 99%